MODEL PARTICIPATORY SOCIAL RESPONSIBILITY ENTREPRENEURS OF COMMUNITY OF CSR PROMOTION OF – BASED TOURISM ENTERPRISES IN PHATTHALUNG PROVINCE - Boonying, Jiraporn; Chantana, Sujitra (Journal of MCU Nakhondhat, 2021)
This research Its objectives are 1) to survey the personal characteristics of the respondents 2) to survey the model of CSR promotion with reputation, image and participation 3) to find the relationship between model of CSR promotion and reputation And participation Of participatory community tourism enterprises The researcher has specified the research methodology. Is a combined research The sample consisted of 400 people. The tools used were questionnaires and in - depth interviews. The statistics used for data analysis were frequency, percentage, mean, standard deviation. Finding relationships person’s. The results of the research revealed that 1) Most of the respondents were female. Accounting for 75.8%, aged between 41 - 50 years, accounting for 58.0%, marital status accounting for 63.50%, having bachelor degree education Accounting for 79.0 percent of the total, occupation 34.8 percent, with monthly incomes of 10,001 - 20,000 baht or 34.8 percent 2) The level of opinion on CSR promotion found that The overall high level in most of the cases were found. Responsibility to ethics Most are average , followed by the responsible law the image as a whole at a high level. The model of CSR promotion that is suitable for image, followed by reputation Relations between model of CSR promotion shows that participation does not have a relationship with the image , reputation. In relation to the model of CSR promotion with statistical significance at the level of 0.05 Your feedback and opinions are in the same way that the general standards and the private sector must be encouraged. Participatory community tourism enterprise entrepreneurs For activities to occur regularly Must promote and develop the environment and preserve the nature of the tourist attraction to be outstanding, unique and preserve the beautiful image of Thai